Expert online coaching for menopause : a qualitative investigation into the effectiveness of a multi-disciplinary wellness coaching intervention : a thesis presented in partial fulfilment for the degree of Master of Science in Nutrition and Dietetics at Massey University, Albany, New Zealand - Irwin-Gordon, Karis (Massey University, 2025)
Introduction: Menopause is a biological process that all women will traverse as they age into midlife. Physical, emotional, and mental changes are the hallmark of this process, with some women requiring intervention to improve quality of life. Aim: This pilot study had two aims. The first was to explore the lived experience of women with menopause. The second was to qualitatively evaluate the effective components of a menopause wellness coaching intervention and its implementation. Methods: Semi-structured interviews were conducted with women who enrolled in the wellness coaching programme pilot. Interviews were conducted prior to beginning the programme (baseline), and halfway through the programme (midpoint). They were conducted from June to September 2025. Interviews were audio recorded, transcribed, and thematically analysed. Results: 12 women were interviewed in total (12 at baseline, seven at midpoint). Baseline interviews identified four key themes for women’s experience with menopause: lack of knowledge of menopause, menopause as a taboo topic, impact of menopause on daily life, wanting to feel supported with menopause. Midpoint interviews identified four key themes from engagement with the programme: a need for empathetic coaching, barriers to engaging in behaviour change, practical tips to enhance lifestyle, and improvement in holistic wellbeing. Women all reported a lack of knowledge of menopause and found that engagement in the programme was facilitated due to the empathetic approach of the coaches, and there was an improvement in overall wellbeing at the midpoint of the intervention. Findings: The findings demonstrated a landscape for women with menopause which has lacked information, placed a taboo on speaking of it, leading to women struggling with symptoms and seeking support. Wellness coaching interventions can begin to address these pain points, providing women with practical tips and emotional support to manage this stage of their life. Further studies should be conducted to evaluate the impact of a holistic wellness coaching intervention, to identify the total efficacy of wellness coaching programme to improve QoL in women with menopause.
Keywords: menopause; lived experience; wellness coaching; holistic wellbeing; 321004 Nutritional science; 420307 Health counselling